European Islam: The Challenges for Society and Public Policy - Samir Amghar, Amel Boubekeur, Michael Emerson (Centre for European Policy Studies, 2007)
Written by an array of specialists from a number of different countries, this balanced, scholarly assessment examines the state of Europe's Muslim communities, the challenges they face, and the efforts European governments are making to cope with the resulting demographic and cultural changes. In a particularly provocative contribution, the French scholar Olivier Roy challenges much of the conventional wisdom on the subject of Muslim extremism. He argues that the radicalization of Europe's Muslim youth is not directly related to Middle Eastern political crises, pointing out that no Afghan, Iraqi, or Palestinian has been involved in recent terrorist attacks in Europe and that such acts have rarely been tied to events in the Middle East.